2002
DOI: 10.2320/matertrans.43.2449
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Deformation Behavior of Zn-22 mass%Al Alloy with Nanocrystalline Structure

Abstract: The deformation behavior near room temperature in Zn-22 mass%Al alloy including nanocrystalline structure produced with Thermo Mechanical Controlling Process (TMCP) technology has been characterized over a wide range of strain rates from 10 −6 to 10 −1 s −1 at temperatures from 273 to 473 K. The microstructure of TMCP produced Zn-22 mass%Al alloy had both a random distribution of equiaxed Al-rich and Zn-rich phases with grain size of 1.3 µm and many nanocrystalline Zn particles in Al-rich phases. Since the flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 31 publications
(36 reference statements)
4
40
1
1
Order By: Relevance
“…4, which also includes comparative data taken from Ref. (7,24,25,28). The region exhibiting large elongations was roughly in good agreement with the region where high m-values were achieved.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…4, which also includes comparative data taken from Ref. (7,24,25,28). The region exhibiting large elongations was roughly in good agreement with the region where high m-values were achieved.…”
Section: Resultssupporting
confidence: 61%
“…2, which includes the results of earlier reports, 7,20,[24][25][26] as well. The strain rate sensitivity exponent (m-value) is defined in the equation (d ln =d ln _ " ") where is the flow stress and _ " " is the strain rate.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…[3][4][5][6] Especially, the melting point of superplastic Zn-22 mass%Al alloy is comparatively low (693 K), and it has been reported that superplasticity was expressed even at room temperature. [7][8][9][10][11] Recently, it was also demonstrated that superplastic Zn-22 mass%Al alloy could possibly be applied to seismic damping devices, showing higher performance in comparison with that using a low-yield-point steel. 12,13) The seismic damping device formed by machining Zn-22 mass%Al alloy has already been put into actual use in a high-rise building.…”
Section: Introductionmentioning
confidence: 99%